Effects of meteorological factors on the retention of particulate matter in lawn grass blades - Wang, Junrui; Kong, Weihan; Li, Haimei; Sun, Xiaodan; Sun, Yingkun; Liu, Yu (Frontiers in Plant Science, 2025)
Plant leaves can reduce the concentration of atmospheric particulate matter (PM) by absorbing it in the air, and this mitigates the deleterious human health effects of PM. However, the ability of plant leaves to retain dust is limited and varies continually due to various meteorological factors such as rainfall, extreme wind speed, and PM10 concentrations. Here, we measured the ability of seven types of turfgrass with leaves similar in macromorphology but varying in micromorphology to retain dust particles of different sizes; we also analyzed the effects of various meteorological factors, such as rainfall, maximum wind speed, and PM10 concentration, on the ability of leaves to retain particles of different sizes. There were significant differences in the ability of the seven types of turfgrass to retain particles of different sizes; the dust retention capacity of Zoysia sinensis was the strongest(2.04 g·m-2), and that of Festuca elata was the weakest(1.39 g·m-2). The elution rates of PM>10 after rainfall of 3 mm and 4 mm were significantly higher than those of PM2.5-10 and PM2.5; the elution rates of PM>10, PM2.5-10, and PM2.5 increased as the amount of rainfall increased. When the amount of dust on leaves is low, wind promotes increases in leaf PM retention. When the blade retains a certain amount of dust, the maximum wind speed is greater than 9.1 m·s-1, which leads to a decrease in the dust retention of lawn grass blades. The concentrations of PM10 and PM2.5 were positively correlated with the retention of particles of different particle sizes. Therefore, evaluations of the dust retention ability of plant leaves require consideration of the effects of local rainfall, maximum wind speed, PM10 concentration, and other factors.